2011
DOI: 10.1111/j.1526-4637.2011.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Stellate Ganglion Blockade for the Management of Drug-Resistant Electrical Storm

Abstract: The patient was rapidly stabilized following left stellate ganglion blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 10 publications
0
11
0
2
Order By: Relevance
“…LSG block is a percutaneous approach to block the peripheral sympathetic ganglia using local anaesthetics. The technique reduces sympathetically driven cardiac excitability in animal and human studies (Nademanee et al 2000;Loyalka et al 2011;Patel et al 2011). Nademanee and colleagues reported that cardiac sympathetic blockade, including LSG block, is superior to the Advanced Cardiovascular Life Support recommended antiarrhythmic therapy in treating patients with electrical storm (Nademanee et al 2000).…”
Section: Mechanism Of Benefit Of Csdmentioning
confidence: 99%
See 1 more Smart Citation
“…LSG block is a percutaneous approach to block the peripheral sympathetic ganglia using local anaesthetics. The technique reduces sympathetically driven cardiac excitability in animal and human studies (Nademanee et al 2000;Loyalka et al 2011;Patel et al 2011). Nademanee and colleagues reported that cardiac sympathetic blockade, including LSG block, is superior to the Advanced Cardiovascular Life Support recommended antiarrhythmic therapy in treating patients with electrical storm (Nademanee et al 2000).…”
Section: Mechanism Of Benefit Of Csdmentioning
confidence: 99%
“…; Patel et al . ). Nademanee and colleagues reported that cardiac sympathetic blockade, including LSG block, is superior to the Advanced Cardiovascular Life Support recommended antiarrhythmic therapy in treating patients with electrical storm (Nademanee et al .…”
Section: Introductionmentioning
confidence: 97%
“…Nademanee et al .,[3] reported that cardiac sympathetic blockade is superior to the antiarrhythmic therapy in treating ES and have advocated LSGB for reducing the sympathetic surge. There are a few publications on efficacy of the LSGB[67]and thoracic epidural anaesthesia (TEA)[89]in lowering the incidents of ventricular arrhythmias during ES. These therapeutic approaches reduce adrenergic tone that is most likely responsible for the reported efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A change in temperature and sweating pattern of the left upper limb may be a better indicator than development of Horner's syndrome in this regard. Nevertheless, percutaneous stellate ganglion block has been reported to be temporarily effective, in controlling ES in multiple reports [9,10]. This is a promising approach, as it can be performed with relative ease even in unstable patients and thus can help in tiding over the crisis.…”
Section: Pharmacological Lscdmentioning
confidence: 95%